2014
DOI: 10.1371/journal.pone.0097492
|View full text |Cite
|
Sign up to set email alerts
|

Do Editorial Policies Support Ethical Research? A Thematic Text Analysis of Author Instructions in Psychiatry Journals

Abstract: IntroductionAccording to the Declaration of Helsinki and other guidelines, clinical studies should be approved by a research ethics committee and seek valid informed consent from the participants. Editors of medical journals are encouraged by the ICMJE and COPE to include requirements for these principles in the journal’s instructions for authors. This study assessed the editorial policies of psychiatry journals regarding ethics review and informed consent.Methods and FindingsThe information given on ethics re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
0
12
1
2
Order By: Relevance
“…We found that these questions had the highest portion of positive answers and were clearly stated in most journals (0.88, 0.84 and 0.80 for Declaration of Helsinki standards, approval by institutional ethics committee and informed consent, respectively). The discrepancies between our study and the one conducted by Strech et al (2014) could come from the fact that these studies covered two significantly different groups of journals-''Psychiatry'' and ''Medical Laboratory Technology'', each with different procedures and practices. Nonetheless, questions of research ethics should always require proper attention, no matter the research field.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…We found that these questions had the highest portion of positive answers and were clearly stated in most journals (0.88, 0.84 and 0.80 for Declaration of Helsinki standards, approval by institutional ethics committee and informed consent, respectively). The discrepancies between our study and the one conducted by Strech et al (2014) could come from the fact that these studies covered two significantly different groups of journals-''Psychiatry'' and ''Medical Laboratory Technology'', each with different procedures and practices. Nonetheless, questions of research ethics should always require proper attention, no matter the research field.…”
Section: Discussioncontrasting
confidence: 58%
“…Also, we found that instructions for authors in ''Medical Laboratory Technology'' subject group include recommendations concerning ethical research more often than those for editorial policy and research integrity. In a study of 123 psychiatry journals' instructions for authors, Strech et al (2014) reported that only 37 % referred to Declaration of Helsinki, 54 % required or recommended ethics review and 58 % required or recommended informed consent. We found that these questions had the highest portion of positive answers and were clearly stated in most journals (0.88, 0.84 and 0.80 for Declaration of Helsinki standards, approval by institutional ethics committee and informed consent, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst previous studies (e.g. Asai and Shingu 1999 ; Bosch et al 2012 ; Strech et al 2014 ; Horvat et al 2015 ) had typically only focused on instructions for authors, it turns out that quite often the relevant information is required during the later (submission) stage. Notably, three of the 29 journals did not allow the coder to access information concerning the submission process, as they either have submission windows and the access was not allowed ( Philosophy and Phenomenological Research and Nous ) or required submission fees ( Philosophers’ Imprint ).…”
Section: Methodsmentioning
confidence: 99%
“… 14 Recent studies in different fields have shown that instructions to authors in journals often fail to require authors to state that the study was approved by an ethics committee and informed consent obtained from participants; articles also often omit mentioning these points (cf Weil et al 2002 ; Strech et al 2014 ). …”
mentioning
confidence: 99%
“…Sin embargo, no existen estudios que aborden la ética en este campo de forma integral, frente a lo que ocurre en el área biomédica (Bosch et al, 2012;Strech;Metz;Knüppel, 2014;Wu;Zou, 2015).…”
Section: Introductionunclassified